2010
DOI: 10.3109/17482941.2010.513732
|View full text |Cite
|
Sign up to set email alerts
|

Cell free DNA detected by a novel method in acute ST-elevation myocardial infarction patients

Abstract: With this method, CFD levels correlated with the levels of established markers of myocardial necrosis but not with EF. The kinetic pattern of CFD release after STEMI and its prognostic value require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 14 publications
5
39
1
1
Order By: Relevance
“…First discovered in 1948 by Mandel and Metais, fragmented DNA or cfDNA has since been associated with a number of conditions, including end-stage renal disease, myocardial infarction, stroke, and trauma [2][3][4][5][6][7]. Multiple studies have shown a correlation between the levels of cfDNA and cellular injury and necrosis, processes relevant in cancer cell survival and propagation.…”
Section: Cfdnamentioning
confidence: 99%
“…First discovered in 1948 by Mandel and Metais, fragmented DNA or cfDNA has since been associated with a number of conditions, including end-stage renal disease, myocardial infarction, stroke, and trauma [2][3][4][5][6][7]. Multiple studies have shown a correlation between the levels of cfDNA and cellular injury and necrosis, processes relevant in cancer cell survival and propagation.…”
Section: Cfdnamentioning
confidence: 99%
“…27 Levels of ctDNA in blood can vary widely between patients due to differences in tumor DNA release mechanisms and the effectiveness of cfDNA clearance, with estimates of the proportion of ctDNA from total cfDNA varying from 0.01% to 90%. 20,28 Serum cfDNA levels are significantly higher than plasma levels 20,[29][30][31][32][33] due to clotting of white blood cells in the collection tube, leading to their lysis. 20,32,33 Consequently, serum ctDNA is diluted by genomic DNA released from white blood cells, and plasma is preferred as a source of ctDNA.…”
Section: Liquid Biopsy Using Ctdna In Bloodmentioning
confidence: 99%
“…Chang et al [6] used QIAamp blood and PicoGreen cf-DNA kits for the extraction and quantification of serum cf-DNA, respectively, and found that elevated cf-DNA in MI patients could complement troponin (Tn) and creatine kinase-MB (CK-MB) in a multiple marker test format. Furthermore, using a fluorescent assay, Shimony et al [7] found that cf-DNA concentrations were higher in ST-elevation myocardial infarction (STEMI) and were correlated with the levels of established markers of myocardial necrosis such as cardiac Tn I (cTnI) and CK. In addition to these studies, others have demonstrated the prognostic significance of cf-DNA in MI patients.…”
Section: Introductionmentioning
confidence: 99%